2013
DOI: 10.1371/journal.pone.0066226
|View full text |Cite
|
Sign up to set email alerts
|

Development of Novel In Vivo Chemical Probes to Address CNS Protein Kinase Involvement in Synaptic Dysfunction

Abstract: Serine-threonine protein kinases are critical to CNS function, yet there is a dearth of highly selective, CNS-active kinase inhibitors for in vivo investigations. Further, prevailing assumptions raise concerns about whether single kinase inhibitors can show in vivo efficacy for CNS pathologies, and debates over viable approaches to the development of safe and efficacious kinase inhibitors are unsettled. It is critical, therefore, that these scientific challenges be addressed in order to test hypotheses about p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
166
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(181 citation statements)
references
References 47 publications
(75 reference statements)
15
166
0
Order By: Relevance
“…The effect we found on episodic memory is in line with a broad scientific literature that indicates that p38 α in involved in oligomeric amyloid‐beta and inflammation‐induced synaptic dysfunction and to stress‐ and age‐related synaptic dysfunction in the hippocampus 4, 5, 10, 11, 12, 13, 14, 31. In our clinical study, the ES that we saw for immediate and delay recall compares favorably to ES of ≤0.2 for WMS immediate or delayed recall at week 12 in the placebo‐treated subjects in two trials of Souvenaid in a similar patient population (mild AD, baseline MMSE = 24) 32, 33.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The effect we found on episodic memory is in line with a broad scientific literature that indicates that p38 α in involved in oligomeric amyloid‐beta and inflammation‐induced synaptic dysfunction and to stress‐ and age‐related synaptic dysfunction in the hippocampus 4, 5, 10, 11, 12, 13, 14, 31. In our clinical study, the ES that we saw for immediate and delay recall compares favorably to ES of ≤0.2 for WMS immediate or delayed recall at week 12 in the placebo‐treated subjects in two trials of Souvenaid in a similar patient population (mild AD, baseline MMSE = 24) 32, 33.…”
Section: Discussionsupporting
confidence: 90%
“…Traditionally p38 α kinase is considered to be an inflammation‐related target as microglial p38 α promotes production of proinflammatory cytokines6 and modulates microglial activation state,7, 8 and in the healthy state p38 α expression within neurons is low 9. However, more recent findings indicate that neuronal p38 α is increased in disease and under stress, and neuronal p38 α expression has been implicated in amyloid‐beta and/or inflammation‐induced synaptic dysfunction,10, 11, 12, 13, 14 specifically impaired synaptic plasticity. Consistent with the biology of neuronal p38 α , selective small molecule inhibitors of p38 α rapidly (i.e., within 2–3 weeks) reverse spatial learning defects in the APP/PS1 mouse model,15 aged rats16 and in tauopathy (hTau) mouse model 17…”
Section: Introductionmentioning
confidence: 99%
“…To test the effect of PME-1 overexpression on the behavioral impairments that result from acute Aβ exposure, we tested these animals in a hippocampus-dependent contextual fear-conditioning task previously shown to be sensitive to Aβ administration (27)(28)(29). Vehicle-treated animals overexpressing PME-1 exhibited a level of freezing 24 h after training in this task similar to that of vehicletreated single-transgenic control siblings ( Fig.…”
mentioning
confidence: 96%
“…As a second test of the effect of PME-1 overexpression on Aβ-induced cognitive impairments, we tested these animals on a 2-d radial arm water maze task (29,30) and found that PME-1 overexpression also sensitized animals to Aβ-induced impairments in this task. PME-1 overexpression did not affect the performance of vehicle-infused animals, and a subthreshold dose of Aβ did not affect the performance of control animals.…”
mentioning
confidence: 99%
“…In many rodent models including transgenic and non-transgenic rodents, high levels of Aβ peptides (> nanomolar) can dramatically weaken neuronal physiology and synaptic density, which were also distinctive feature of AD [12]. More importantly, excess generation of Aβ peptides induced cognitive dysregulation impairing the animals' performance in learning and memory tasks [16,17]. These findings supported the importance of Aβ hypothesis in AD pathology.…”
Section: Aβ Hypothesismentioning
confidence: 60%